ANALISIS MEDIA PEMBELAJARAN IPAS PADA MATERI ZAT BERBAHAYA PADA MAKANAN BAGI SISWA SEKOLAH DASAR - Aditya Ramadhan; Faqih Hidayah Tullah; Nurul Hasanah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is motivated by the importance of delivering Natural and Social Sciences (IPAS) material effectively and engagingly, particularly on the topic of hazardous substances in food at the elementary school level. Many students have difficulty understanding this material due to its abstract nature and direct link to health. The main problem in this study is students' low understanding of the dangers of using additives and hazardous chemicals in food. This study aims to analyze the effectiveness of using learning media in improving students' understanding of this material. The research method used was descriptive qualitative, with observation, interviews, and documentation as data collection instruments. The results showed that the use of visual and digital learning media, such as videos, interactive images, and infographics, can significantly improve students' understanding and learning interest. Students became more active and were able to identify the types of hazardous substances commonly found in food. Based on these results, it is recommended that teachers consistently use innovative, engaging learning media that are appropriate to the characteristics of elementary school students, and that they be trained in their development and implementation.